Pengaruh Organizational Culture terhadap Teacher Innovation Capability dalam Perspektif Knowledge Sharing: Studi Kasus Jabodetabek - Sucipto Basuki; Masduki Asbari; Agus Purwanto; Eva Agistiawati; Miyv Fayzhall; Fatrilia Rasyi Radita; Siti Maesaroh; Mustofa Mustofa; Sri Wahyuni Asnaini; Gusli Chidir; Winanti Winanti; Ahmad Yani; Eman Singgih; Rachma Nadhila Sudiyono; Francisca Sestri Goestjahjanti; Teguh Yuwono; Dhaniel Hutagalung (Universitas Muhammadiyah Enrekang, 2020)
This study aims to measure the influence of organizational culture on teacher innovation capability in Indonesia mediated by tacit and explicit knowledge sharing. Data collection was carried out by simple random sampling via electronic to a population of teachers in Jabodetabek. The returned and valid questionnaire results were 583 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are organizational culture has a positive and significant effect on teacher innovation capability, both directly and through mediating tacit knowledge sharing. Organizational culture has a positive and significant effect on explicit knowledge sharing. While explicit knowledge sharing has not significant effect on teacher innovation capability. This novel research is proposing a model to build teacher innovation capability among teachers through organizational culture with tacit & explicit knowledge sharing as mediation. This research can pave the way to improve teacher readiness in facing the era of education 4.0.